Membrane technologies and applications - Mohanty, Kaustubha; Purkait, Mihir K. (Boca Raton , FL : CRC Press, 2012)
'Membrane technologies play an increasingly important role in unit operations for resource recovery, pollution prevention, and energy production, as well as environmental monitoring and quality control. They are also key component technologies of fuel cells and bioseparation applications. Membrane Technologies and Applications provides essential data and background information on various dimensions of membrane technologies, with a major focus on their practical application. Membranes of inorganic materials offer cost-effective solutions for simple to complex separation problems. This book is designed for anyone interested in water and wastewater treatment, membrane suppliers, as well as students and academics studying the field'--
'This book is written to provide in one place the essential data and background materials on various aspects of membrane technology with a major coverage on application. It is intended for the following technologists so they do not need to gather scattered information from the current and past literature: industrial as well as situational researchers, application scientists and engineers with an interest in membrane technologies and students pursuing advanced separation studies'--
Includes bibliographical references and index.
Keywords: Membrane separation; Membranes (Technology)